Transformer 2 alpha homolog is a downstream gene of hypoxia-inducible factor 1 subunit alpha and is involved in the progression of pancreatic cancer. Issue 5 (2nd May 2022) - Cao, Wenpeng; Lei, Shan; Zeng, Zhirui; Xiao, Chaolun; Sun, Baofei; Xie, Peng; Li, Yumei; Luo, Daopeng; Yu, Wenfeng
ABSTRACT: Intratumoral hypoxia is a common feature of pancreatic cancer (PC) and also plays a role in its progression. However, hypoxia-regulated signatures in PC are still not completely understood. This study aimed to identify core hypoxia-associated genes and determine their underlying molecular mechanisms in PC cells. Transformer 2 alpha homolog (TRA2A) was found to be an important hypoxia-associated gene, which was upregulated in PC tissues and in PC cells cultured under hypoxia. High TRA2A expression was associated with advanced stage, poor differentiation, and lymph node metastasis. Under normoxic and hypoxic conditions, knockdown of TRA2A both markedly suppressed PC cell proliferation and motility in vitro and in vivo, as well as activation of the AKT pathway. Hypoxia-inducible factor 1 subunit alpha (HIF1α) upregulated the transcription of TRA2A by directly binding to its promoter. TRA2A showed a co-expression relationship with HIF1α in PC tissues. Overexpression of TRA2A alleviated the pro-inhibitive functions of HIF1α-inhibition on PC cell proliferation and motility under hypoxia. In conclusion, TRA2A is a crucial downstream gene of HIF1α that accelerates the proliferation and motility of PC cells. TRA2A may be a novel and practical molecular target for investigating the hypoxic response of PC cells. Abbreviations : TRA2A, transformer 2A protein; PC, pancreatic cancer; HIF1α, hypoxia-inducible factor 1-alpha; GEO, Gene Expression Omnibus; IHC, immunohistochemical staining. Graphical abstract: uf0001